LASER toy-induced macular burn: An illustrative case - Elbarghathi, Adam; Abdullah, Ruwida (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Introduction: Light amplification by stimulated emission of radiation (LASER) toys are widely available in the market with no clear information about their wavelength and hazardous effects. To be safe to the eyes, LASER should be classified <3b (according to international safety classification). Case History: We here report an illustrative case of macular injury post LASER toy direct exposure. A 12-year-old boy, previously known hypermetrope with left-eye (LE) amblyopia, presented complaining of drop of vision in the right eye (RE) after his colleague pointed a LASER toy directly over his RE. His corrected visual acuity (VA) was 5/60 (amblyopic) in the LE and 6/18 in the RE. The anterior segment was normal in both eyes. Fundus examination showed the LE to be normal, and the RE had a macular yellowish, oval-shaped lesion. Optical coherence tomography and fundus picture revealed central macular burn. Local and systemic corticosteroids were prescribed tapering over 9 days. After 1-week, the patient noticed some improvement in VA in RE to 6/9. Conclusion: LASER toys available in several markets are reported to be vision threatening and cause macular burn which responds partially to corticosteroids. More education and strict regulation of distribution and use of LASER toys and instruments is urgently needed.
Keywords: Corticosteroids; LASER toys; macular burn